The appetite for online coach education: Now and the future (2013)
This report details the key findings from a survey of around 500 coaches who were asked about their usage and preferences for online resources to help develop their coaching knowledge and practises. The research was carried out to provide sports coach UK and its partners with market intelligence to assist with future decisions on the format of educational and developmental resources.